RESEARCH ON MULTIPLE FAILURE MODES FOR RELIABILITY CALCULATION IN CRACK GROWTH LIFE BY SQP METHOD - SUN YuanTao; ZHANG ZengZeng; ZHANG Qing; QIN XianRong (Jixie qiangdu)
The fatigue crack growth（FCG） phenomenon always exists in large mechanical structural. Influenced by varied kinds of random factors, the safety evaluation of structure in FCG is under great uncertainty. Based on the reliability theory, this article derived the joint limit state equation of fatigue failure and static strength failure, and the parameters which have great influence on the fatigue crack growth rate（load level, crack initial length and material parameter） were selected by the sensitivity analysis. And then these parameters were regarded as random variables. On this basis, the optimization mathematical model of reliability index was established, and then the reliability index under the multiple failure modes of structure was calculated in every cycle based on the SQP method. A specific computation example was given, and the curve of reliability criterion in multiple failure modes was used to compare that in single failure mode. The results indicated that the reliability analysis based on multiple failure modes was reasonable, and the evaluation of reliability could be obtained in fatigue crack growth process.